A study on physical activity in shift workers in an urban city of India - Das, Shubhabrata; Das, Munmee; Ray, Shomik (International Journal Of Community Medicine And Public Health, 2019)
Background: Physical inactivity has been identified as one of the leading risk factors for non-communicable diseases. Several studies have established the fact that shift working is associated with various non communicable diseases. Studies assessing the knowledge, attitude and practice towards physical activity amongst shift workers is almost non-existence even though it has been established that mediators like knowledge and attitude affect healthy behaviour and adoption of health improving behaviour. Thus this study aims to assess the knowledge-attitude-practice of physical activity among shift workers in Gurugram city which is the centre of various BPO/KPO companies in India. Methods: The present study is an organization based cross sectional study. Interviewer administered questionnaire were used to capture information on physical activity. Information on knowledge and attitude was collected using a piloted and pretested questionnaire. Practice of physical activity was collected using global physical activity questionnaire (GPAQ). Descriptive and linear regression analyses were performed using Ms-Excel and STATA (13). Results: Our study found that nearly fifty percent of the study participants were physically inactive and only 18% of the study participants knew recommended minimum weekly intensity of physical activity. Physical activity was found to be significantly associated with overall knowledge score (p<0.01). Conclusions: Knowledge regarding physical activity among the study participants was not adequate as reflected in their physical activity practice, hence knowledge and awareness towards physical activity should be enhanced to prevent non communicable diseases amongst the shift workers.